The Euro as a Polity: Karl Polanyi in Frankfurt? - Thomasberger, Claus (Global Perspectives, 2020)
As factors of production, labor, money, and land play a role in economics that is rarely understood. The difficulty of deriving the contribution of the individual factor of production to the value of jointly produced final commodities (the famous “problem of imputation”) occupied generations of Austrian economists (Hayek 1984) and inspired Ludwig Mises to produce his 1920 article “Economic Calculation in the Socialist Commonwealth” (Mises 1935). Any attempt at rational socialist planning is utopian, Mises argued, because only price-making markets for the factors of production provide the information for economically rational decision-making. If the birthplace of neoliberalism was, as Slobodian (2018, p. 30) put it, Ludwig Mises’s office in the Vienna Chamber of Commerce, this article was its moment of birth.Karl Polanyi was one of the first to respond, doing so in the same journal in which Mises’s piece had been published, the Archiv für Sozialwissenschaften, long before Friedrich Hayek, Walter Lippmann, Lionel Robbins, and German ordoliberals such as Alexander Rüstow and Wilhelm Röpke intervened (Polanyi 2016, 2018b). In his contributions to what became the famous socialist accounting debate, Polanyi outlined his idea of a society’s “constitutional form … as a relationship of mutual recognition” (Polanyi 2018a, 54) based on direct cooperation between consumers and producers, as well as a functional democracy.Two decades later, Polanyi resumed this discourse with a more radical critique, making use of Mises’s argument for his own end (cf. Thomasberger 2020). Mises’s case for price making markets is no less utopian than the central planning model, he argued in The Great Transformation (TGT). The crucial point, Polanyi contended, is that the factors of production are fundamentally different from genuine commodities. Polanyi drew on a line of reasoning put forward by the sociologist Ferdinand Tönnies (2001, p. 81-82) and by Mises’s intimate enemy, the Austrian economist Friedrich Wieser (1927, p. 175-77), who was inclined toward Fabian socialist ideas. Given that the factors of production are not (and cannot be) produced for sale by private enterprises, the commodity form of labor, money, and land is fictitious.Polanyi’s category fictitious commodities is the pivot of Klein’s paper. This starting point allows him to go beyond the common interpretation of Polanyi’s work, which focuses on the dichotomy of market opening and social closure, and to address instead a more profound problem: the conflict between capitalism and democracy. Such a reading is indeed closer to the core of the Polanyi approach, which refers to a society that “transcends the self-regulating market by consciously subordinating it to a democratic society” (Polanyi 2001, 242). Not social protection, but democracy, is the alternative to the self-regulation of the market. Polanyi never believed that protection could achieve more than a temporary stabilization of market society. In fact, it is somewhat paradoxical that in the discussion about the contradictions of European integration, Polanyi is celebrated as a defender of societal closure, while he himself expressed the conviction that the protective measures “impaired the self-regulation of the market, disorganized industrial life … and finally disrupted the social organization based upon it” (Polanyi 2001, 4). From the point of view of the conflict between capitalism and democracy, the institutions that result from the attempt to commodify labor, money, and land are crucial because they are, as Klein puts it, the “point of entry of political power into the economic sphere” (Klein 2020, 11). Concerning the debate about the crisis of European integration, this is a rather unexplored terrain.In what follows, I will not discuss the question of whether the category fictitious commodities can be fruitfully linked to the idea of premodern modes of economic integration, a connection that Polanyi himself never established. Instead, I will concentrate on two issues that Klein’s paper raises without discussing them explicitly. The first question is: What if the creation of a self-regulating market system becomes the dominant political goal? What if, for example, the central bank is transformed into a market maker for money on political grounds? The second point seems to me even more important. Europe is not a nation. However, “in Polanyi’s schema, the self-regulating market was a national economic institution” (Polanyi-Levitt 2013, 89), which linked the “rest of the world” to England by a “golden straightjacket,” as Polanyi’s daughter, the development economist Kari Polanyi Levitt, remarked. In TGT even European colonialism plays only a marginal role. As a result, European integration after World War II raises issues that Polanyi did not discuss in depth. I will proceed in two steps: First, I will reconstruct some essential points of Polanyi’s analysis. Following this, I will pose the question of how to apply his analysis to Europe.From the point of view of a market system, the crux of the factors of production—or the fictitious commodities, as I shall hereinafter refer to them—is that, on the one hand, private enterprises must be enabled to buy labor, land, and money on a market. On the other hand, private companies are notcapable of producing and selling the fictitious commodities. The difficulty is obvious: In a market economy, enterprises depend on markets for the fictitious commodities, but such an economy is unable to produce them. This means that the market system depends on external forces. Certainly, this is also true for other institutions and social infrastructures that only the state can provide. However, the fictitious commodities are different in that they cannot be understood as part of the extra-economic framework. Labor, money, and land are economic factors; they are the condition sine qua non of the market system. No self-regulation is conceivable without including the fictitious commodities. What legal scholars with regard to the secular state call the Böckenförde dilemma in the case of fictitious commodities affects economic liberalism directly. The market system is unable to produce and reproduce itself spontaneously. The economic mechanism lives by prerequisites it cannot create. Social institutions are required to provide what for the functioning of a market system is indispensable. Only society can provide the commodities on which a market economy is based. Therefore, in a market society, the economy is not—and can never be—a functional machinery. “Laissez-faire economy was the product of deliberate State action,” as Polanyi (2001, p. 147) stated, summing up the nineteenth-century answer to the dilemma. The different institutions that coordinate economic activities are the outcome not of functional pressure but of a political struggle around the (de)commodification of the fictitious commodities. “Market economies are polities,” to paraphrase the felicitous title of a book edited by Christian Joerges, Bo Stråth, and Peter Wagner (2005).In other words, an ideal market society presupposes the political creation and regulation of particular social institutions whose purpose is to simulate market conditions. Unemployment insurance, health care, union legislation, central bank acts, land property rules, and environmental regulations are indispensable for transforming labor, money, and land into commodity-like entities. Here a conflict between the social nature of the task and its economic role arises. From the perspective of the market system, these institutions fulfill the function of market makers. However, from the viewpoint of society, they allow for various forms of political regulation and economic planning, taking into account the social needs of the different strata of society. It is this tension between their political roots and their economic function within the market system that puts these institutions at the center of the political struggle. Since law cannot ignore prevailing ideals, worldviews, and external expertise, it plays a contradictory role in this process, functioning as a vehicle for commodification and political regulation.In TGT Polanyi showed that from the beginning, law played a key role in the process of commodification. In England, three legal regulations were crucial:Even if a market society presupposes the commodification of all three fictitious commodities, for reasons of space I will concentrate on money. The crucial point is to understand that the nineteenth-century gold standard was primarily not an economic but a political system.In the first decades of the century, substantially inconvertible paper money circulated in England. The commercial banks—and their theoretical advocates, the so-called Currency School—pushed for the right to provide money according to the banks’ calculations. In contrast, the supporters of the Banking School argued that this would lead to the risk of an overissuance of notes. The essential feature of the banking system created by the abovementioned Peel’s Bank Act was to keep the supply of money artificially scarce by linking the amount of banknotes to the quantity of gold in the issuing department of the Bank of England (BoE). By law, political control and the discretionary influence of the government on money and banking were reduced to a minimum.Over the course of the century, the commodification of labor, money, and land in England set in motion a transformation on a global scale. Relying on bank money, the market system generated a previously unknown social and economic dynamic. In the last decades of the “long” nineteenth century, Polanyi (2001, p. 136) commented, “a new way of life spread over the planet with a claim to universality.” The international gold standard gave birth to a worldwide system, in which the constitutional regimes became almost the corollary of the gold standard.Here we can observe in outline two problems that we encounter again in Europe today: (1) Given the legislation that forced central banks to limit the supply of money, the international gold standard not only limited the British government’s room for maneuver, but it confined also, and often even more strictly, the policy space in the other countries. The open market for money and finance created international economic and political interdependencies, which reached deeply into society and undermined democratic aspirations. Social legislation, labor unions, and budgetary and monetary policy were forced to accept the priority of the external monetary stability even if this was in contradiction to national interests. (2) The variety of socioeconomic environments, institutional traditions, and sociopolitical objectives in different countries was negated. The gold standard forced the individual countries to adapt to the liberal economic model with its universal aspirations.The BoE functioned as the conductor of the global monetary orchestra. Polanyi introduced two categories to describe the international dependencies in this period: “anarchistic sovereignty and ‘justified’ intervention in the affairs of other countries” (Polanyi 2001, 261). On the one hand, sovereignty was “anarchistic” insofar as under the gold standard and the prevailing system of unregulated foreign trade, governments lacked any power with respect to international economic affairs. The treatment of trade as a relationship between private undertakings made effective international (political) economic cooperation between states impossible. On the other hand, interventions were “justified” whenever the budgets, finances, and currencies of debtor countries required control. Given the rigidities of the economic system, Polanyi underlined that “the peoples of the world were institutionally standardized to a degree unknown before” (Polanyi 2001, 261).At the same time, however, the inelasticity of the gold supply resulted in a deflationary bias that spread over the world. Even if central banks tried to introduce some doses of flexibility, the system required the adjustment of wages and prices to the current account balances, affecting both the opportunities for profit and the living conditions of large sections of the population. Such a rigid system could survive, Polanyi summarized, only as long as popular democracy was suppressed. Confronted withIn nineteenth-century England, the gold standard and popular democracy were irreconcilable. This explains why attempts to restore the former in the 1920s were bound to fail. Barry Eichengreen took up Polanyi’s point when he pointed out that after the First World War, “the spread of universal suffrage and … the consequent politicization of the policy environment … had destroyed the viability of the gold standard itself” (Polanyi 2001, 233–34). As long as prosperity prevailed, the conflict could be contained. Not so in crisis situations. The restored international gold standard collapsed in 1931.The European Monetary Union (EMU) is at the heart of current debates on the crisis of European integration. Whether Streeck (2014, p. 185) calls the EMU “a political mistake” or Habermas (2012, p. 3) criticizes the “construction flaw of a monetary union,” they share a focus on the Maastricht process. Obviously, this interpretation ignores the fact that the crisis also includes countries—among others the United Kingdom, Poland, and Hungary—that have never been part of the EMU.If we look at the crisis from Polanyi’s perspective, the focus shifts. Not the EMU but the Single European Act, signed in 1986, emerges as the turning point. The single market program was by no means the deregulatory exercise that the European Commission had presented it as being. It was about developing competition throughout the European Union, including markets for labor, land, and money. The novel feature of the program was that it aimed at creating cross-national markets for the fictitious commodities between democratically constituted countries. This is not to say that markets for genuine goods do not cause interdependencies; however, the political character of the process of commodification of the fictitious commodities produces interdependencies of a different quality. Economic, monetary, fiscal, income, and social policy decisions in one country affect directly all other countries participating in the single market. They create political interdependencies, which, if we take Habermas’s understanding that “democratic self-government means that the addressees of mandatory laws are at the same time their authors” (Habermas 2012, 14), is incompatible with national democracy.Why did Jacques Delors and the European Commission nevertheless argue for the creation of Europe-wide markets for the fictitious commodities? Did they underestimate the political costs? Or did they believe that the economic benefits outweighed the loss of political self-determination?It is important to keep in mind that the discussions within the economic discipline never led to the consensus that the European Commission assumed. David Ricardo (1817) had already argued that markets for production factors are by no means necessary in order to enjoy the advantages of the international division of labor. In the twentieth century, declared supporters of free trade such as Gottfried Haberler (1930) and Jagdish Bhagwati (1998) took the same line. Recently, an IMF Staff Paper evaluating empirical studies on the effects of financial globalization concluded that there is evidence not of direct economic gains but rather of political effects: “Our interpretation of the newer literature is that … financial openness can … impose discipline on macroeconomic policies” (Kose et al. 2009, 10). In Europe, the internal market program was met with strong approval by the neoliberal camp. It is reasonable to assume that with the single market, Europe made the political turnaround that the Anglo-Saxon world had already accomplished with Thatcher and Reagan.Be that as it may, the commodification of labor, land, and above all money changed the rules of the game.1 To remain within the context of monetary relations: Open financial markets transformed the European Monetary System (EMS) into an arrangement that came close to what McKinnon (1988) had defined as the “gold standard without gold.” Although the EMS was intended as a symmetrical arrangement, under the conditions of open financial markets the most hard-nosed national central bank, the Deutsche Bundesbank (DBB), assumed the role of a kind of European central bank. The monetary authorities of other European countries were forced to adapt. Recall that in autumn 1992, the conflicts that arose out of these political dependencies nearly put an end to European monetary integration. The different conditions—most European countries were in recession, while Germany was experiencing the unification boom—placed incompatible demands on monetary policy. In this conflict, the DBB acted not as a European but as a German central bank, raising interest rates to record levels. In September 1992, the system faltered. The Italian lira and the pound sterling were forced out of the exchange rate mechanism. Great Britain definitively turned its back on monetary integration, while in Italy a political earthquake shook the party-political landscape.Streeck (2014, p. 186) calls for “a new European monetary system” built on Keynes’s model of fixed but adjustable exchange rates. Now, Keynes was well aware of the fact that systems such as the Bretton Woods System (or the original EMS) are incompatible with transnational financial markets.2 They can function only as long as capital movements are politically controlled. The internal market program destroyed these conditions.Fatally, the Maastricht Treaty did not pursue the goal of reducing political interdependencies but was limited to replacing asymmetry with the all-encompassing dependence on a supranational, technocratic institution that is apparently separate from the political sphere. The German economist Horst Sievert (1993, p. 18) exposed the core idea of the EMU when he remarked, “What is decisive, is that in the monetary union the individual state must pay its debts with money that it cannot produce itself.”3 In the European type of monetary union, not the political authorities but technocrats and private financial institutions control the currency in which public debt is denominated. While in countries with their own currencies the government can turn to its central bank in a time of need, in the EMU, as we have seen in the case of Greece, state bankruptcy becomes a real threat.The financial and economic crisis has revealed the utopian character of the idea of imposing discipline through markets. To touch on just two aspects: (1) Since then, the socioeconomic heterogeneity between the countries has found new forms of expression. By creating long-term interest rate differentials, the crisis has spatially divided what was conceived as a single European capital market. Paradoxically, those countries most dependent on cheap credit are penalized by less favorable financing conditions. (2) If the demand for money and credit is insufficient, efforts to keep the money supply scarce lose their purpose. Neither the Public Sector Purchase Program (PSPP) adopted in 2015 nor the Pandemic Emergency Purchase Program (PEPP) can be derived from theoretical principles based on the commodity fiction of money. The coronavirus crisis is, as Peter Bofinger (2020) suggests, “the hour of Modern Monetary Theory”—an approach that until recently was marginalized by mainstream economics because it regards money not as a commodity but as a means of payment.To overcome the crisis of European integration, two alternatives are usually proposed: deepening integration, “an ever closer union,” or downscaling of integration, defending democracy on the nation-state level. More than seven decades ago, Polanyi already envisaged a third possibility: political cooperation between self-determining nations. Polanyi was in favor of (a) the international division of labor and (b) the liberty of the individual countries “to organize national life at will” (Polanyi 2001, 262). He was (c) aware that both could be achieved only if the commodification of labor, money, and land was restricted. His ideas were indeed aimed at politically controlled regional cooperation between countries that would maintain and develop their particular characteristics. In the final chapter of TGT, he highlighted:The link between the removal of the fictitious commodities from the market and the emergence of a variety of new societies is the crucial point. In another well-known essay published shortly after TGT, Polanyi outlined his idea of a global economic order by contrasting his concept of “regional planning” with that of “universal capitalism” (Polanyi 2018b). For Polanyi, a variety of human societies was not only a fact but also a normative value. It must suffice here to recall his last project, the magazine Co-Existence, which explicitly aimed at the strengthening of peaceful international cooperation.4From this perspective, the debate on the ECB cannot be limited to questions of Outright Monetary Transactions, negative interest rates, state financing, and price stability. The question of how the monetary authorities of a heterogeneous European Union can and should act has to go back to the root problem, the commodification of money. To bring Polanyi’s ideas to Frankfurt would mean at least:However, from the point of view of the commodity fiction, the erosion of the predominance of formal legal rules in the mid-1980s, the emergence of the “regulatory state,” the turn toward governance, and finally the spread of “executive managerialism” (Joerges and Weimer 2013) since the financial crisis appear as a series of functionally necessary adjustments to an originally incomplete regime. As long as this vision prevails, the tensions between increasingly technocratic rule and democratic control are likely to persist. In the light of Europe’s ever-growing diversity, a fundamental redesign of the project, including a reconceptualization of European law that overcomes the fiction of an apolitical integration process, is necessary and, indeed, overdue. Polanyi’s analysis can provide the economic and sociological premises for such an endeavor. However, his writings also show that, especially in the twentieth century, social transformations that would have been necessary proved impossible to implement. We should be prepared; the possibility of some kind of “fundamental shock” to the integration project cannot be ruled out.Claus Thomasberger is a sociologist and economist whose main fields of research are political philosophy, history of economic thought, international political economy, European integration and social ecological transformation. Until 2017, he was Professor of Economics and Foreign Economic Policy at the Berlin University of Applied Sciences. He has been a visiting Professor at the University of Knoxville, the Duke University, and the Vienna University of Economics and Business. He is a member of the Board of the Institute for Ecological Economy Research, Berlin, the International Karl Polanyi Society, Vienna, and of the Executive Committee of the Karl Polanyi Institute of Political Economy, Montreal. Among his publications are: Chronik der großen Transformation, Artikel und Aufsätze von Karl Polanyi 1920-1947 (3 vol.) (with M. Cangiani and K. Polanyi Levitt), 2002-2005; Der neoliberale Marktdiskurs (with W. Ötsch), 2009; Das neoliberale Credo, 2012; Auf der Suche nach dem Ökonomischen (with R. Lucas and R. Pfriem), 2018; Karl Polanyi’s Vision of a Socialist Transformation (with M. Brie), 2018; Karl Polanyi. Economy and Society. Selected Writings (with M. Cangiani), 2018.
Publisher: University of California Press